Secondary multiplication of somatic embryos in banana (Musa spp. AAA) in semisolid medium: effect of the culture vessel type and sterilization method - Kosky, Rafael Gómez (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
<!-- [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--> The objective of this work was to evaluate the influence of the type of culture vessel, and sterilization method on secondary multiplication of somatic embryos of the banana cultivar Grande naine (AAA) in semisolid culture medium. From 200 µl of embryogenic cell aggregates, somatic embryos in the globular stage were formed, which were used in the experiments to compare the types of culture vessel (glass and plastic) and the form of sterilization humid heat (autoclave) and chemical (Vitrofural). The evaluations of the number of somatic embryos that were multiplied were done at 15 and 20 days of culture. The results obtained with respect to the multiplication phase were highly promising, 40.25 and 80.15± 5.0 somatic embryos at 15 and 20 days of culture in glass vessel with plastic cover and using the autoclave as the sterilization method. The results presented in this work open the door for the use of this phase in the mass propagation protocol of this crop via somatic embryogenesis. <!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->